Исследования Восточно-Крымской (Феодосийской) экспедиции в 2009 г. - Бочаров, С.Г.; Новиченкова, Н.Г.; Горбунов, В.И. (Археологічні дослідження в Україні, 2010)
In 2009, the Eastern Crimean (Theodisian) Expedition studied the southern slope of a hill Kordon-Oba (Theodosia city council), a territory to the east from the Ponomarivka settlement (Simeiz local council), and a fortification Ruskofil- Kale of the second half of the 12th c. and the 13th c. on the Martyan Cape (the territory of Nikitsky Botanical Garden).